AUTOMATION CONFIGURATION FOR A TYPICAL ACADEMIC LIBRARY SETTING IN NIGERIA (2015)
This article examines the adoption and implementation of automation configuration in academic libraries in Nigeria. A discussed concept of Automation, library automation, library automation system, components of a typical academic library automation system, functions automating library, cost implications of library automation, available options to library automation system. Also issues such as addressing bibliographic standard in implementing automation, data conversion and bar-coding, methods of barcoding the library collections, patron data conversion bar-coding, staff training, library automation system management cycle (LASMC) also explained. A typical library Local Area Network (LAN) Configuration System, library automation system configuration with Internet Access, advantage and limitation of implementing automation, the digital library concepts and also discuss recommendations are therefore proffered that the operations of a library be it academic, public or special; get a quantum jump with the adoption and implementation of automation initiative